A 4-days-on and 3-days-off maintenance treatment strategy for adults with HIV-1 (ANRS 170 QUATUOR): a randomised, open-label, multicentre, parallel, non-inferiority trial. Issue 2 (February 2022) - Landman, Roland; de Truchis, Pierre; Assoumou, Lambert; Lambert, Sidonie; Bellet, Jonathan; Amat, Karine; Lefebvre, Bénédicte; Allavena, Clotilde; Katlama, Christine; Yazdanpanah, Yazdan; Molina, Jean-Michel; Petrov-Sanchez, Ventzislava; et al.
Summary: Background: Intermittent (on 4 days per week) antiretroviral therapy (ART) for patients with HIV-1 might be more convenient, better tolerated, and cheaper than continuous treatment. We aimed to establish the efficacy and safety of a 4-days-on and 3-days-off (intermittent) maintenance regimen versus a standard 7 day (continuous) maintenance regimen. Methods: In a randomised, open-label, multicentre, parallel, non-inferiority trial, we randomly assigned (1:1) adults with HIV-1 infection with a plasma viral load (pVL) of less than 50 copies per mL for more than 12 months and no drug-resistance mutations to either the intermittent regimen or their existing continuous maintenance regimen, with stratification according to third therapeutic agent (protease inhibitor, non-nucleoside reverse transcriptase inhibitor, or integrase-strand transfer inhibitor). Participants were recruited from 59 hospitals throughout France. The main exclusion criteria were CD4 cell count lower than 250 cells per μL and chronic hepatitis B virus infection. The primary endpoint was the proportion of participants in the modified intention-to-treat (mITT) population who started the study strategy presenting treatment success at week 48 (pVL <50 copies per mL without strategy modification), estimated using the US Federal Drug Administration snapshot approach, with a 5% non-inferiority margin. The study was registered with ClinicalTrials.gov (NCT03256422 ) and EudraCT (2017-000040-17). The trial is now closed. Findings: From Sept 7, 2017, to Jan 22, 2018, 850 potential participants were screened for eligibility. 647 participants were enrolled and randomly assigned (1:1) to either the intermittent or the continuous treatment group. The mITT population included 636 participants (318 per group). At week 48, in the mITT population, treatment success was recorded in 304 (96%) of 318 participants in the intermittent treatment group and 308 (97%) of 318 in the continuous treatment group (adjusted difference –1·3%, 95% CI –4·2 to 1·7). Six (2%) participants in the intermittent treatment group and four (1%) participants in the continuous treatment group had virological failure. Grade 3–4 adverse events were reported in 29 (9%) participants in the intermittent treatment group and 39 (12%) participants in the continuous treatment group (p=0·320). Daily life satisfaction improved in 153 (59%) of 258 participants in the intermittent treatment group versus 19 (7%) of 255 in the continuous treatment group (p<0·0001). ART costs were 43% lower in the intermittent treatment group than in the continuous treatment group (p<0·0001). Interpretation: These findings show the non-inferiority of the treatment strategy of 4-consecutive-days-on and 3-days-off strategy maintenance regimen relative to standard continuous ART triple therapy over 48 weeks. 4 days on and off treatment represents a workable, effective alternative strategy for patients with high adherence to ART, and using a drug combination with a high genetic barrier to resistance. Funding: Institut National de la Santé et de la Recherche Médicale Agence Nationale de Recherche sur le Sida et les Hépatites Virales, Maladies Infectieuses Emergentes.